THE EFFECT OF NET INCOME AND STOCK PRICE ON DIVIDEND DISTRIBUTION IN TELECOMMUNICATION SUB-SECTOR COMPANIES - Suryaningsum, Sri; Ayusulistyaningrum, Dyah; Nugroho, Ginanjar Setyo (Count : Journal of Accounting, Business and Management, 2023)
This research aims to analyze dividend distribution in companies in the telecommunications industry sub-sector. There are two hypotheses tested, namely net profit and share price which are thought to influence dividend distribution. The data used is data for 2022, 2023 and 2024. This paper is important because it will be the basis for investors in maximizing dividend returns in their stock investments. The research objects analyzed are companies in the telecommunications industry sub-sector. The data used is data on net profit, share prices and dividends. The results of this literature review show that there is dividend distribution for companies that have net profits. The results of this literature review are the basis for deriving a hypothesis. In further research, the existence of the hypothesis in this paper will be tested empirically. The results are that for companies in the Telecommunications Industry Sub-Sector with financial report data for 2022 and 2023, stock prices for 2023 and 2024, and dividend distribution for 2023 and 2024, it can be concluded that the first hypothesis is that net profit has no effect on dividend distribution and for the second hypothesis that share prices have an effect. on dividend distribution.